(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Ayurveda is an ancient traditional system of treatment that was born in India, and it has been inducing global curiosity for its potential applications on skin diseases. This systematic review analyses the efficacy and safety of Ayurvedic treatments for common skin diseases, including psoriasis, eczema, or atopic dermatitis (AD), and acne vulgaris. We review the current literature and clinical trials in an attempt to understand contemporary mechanisms of action of key Ayurvedic herbs/formulations and their therapeutic actions (monotherapy as well as consonance with conventional dermatological therapies) on various skin diseases. Studies on patients with chronic skin disease were excluded from this literature search, which represented other potential target populations that could benefit most from the effects of Ayurvedic formulations. Our findings show some positive results in symptom reduction and quality-of-life enhancement for valid trials among people with a variety of long-term disabilities caused by severe skin diseases. Herbs such as Aloe vera, turmeric, and neem for their anti-inflammatory properties have been found to possess significant antibacterial effects, which make them useful in the treatment of skin disorders. But the research also suggests that more well-organised clinical trials in larger populations need to be conducted with concerted efforts in preparing consistent post-extraction grafting techniques and dosages. We also touch on quality control concerns and herb-drug interactions that should be approached with care. This study highlights the potential of Ayurvedic medicine as an adjuvant tool in dermatology and reinforces the importance of integrating an evidence-based approach with conventional medical modalities for better patient outcomes and safety.